India's East Asian outreach. (2nd January 2021) - Mitra, Ryan Milan
ABSTRACT: India's ambitions in East Asia are evident and pragmatic. It has a growing bonhomie with Japan to collaborate with on bilateral level and within multilateral frameworks as well. In consideration of Japan's caution towards the US and China, it is looking for a sustainable partnership that has mutually appreciative policy axes and the capabilities to achieve bilateral objectives with it. It has repeatedly identified India as the most viable option to adopt this role. The author has taken into consideration multilateral arrangements and larger international relations with countries like China to understand the limitations to Indo-Japanese relations, with recommendations on how to overcome them. Furthermore, the article explores the possibility of a larger multilateral security regime with the Republic of Korea and Taiwan, in light of mutual interests and the latest trends of multilateralism that have swept Asia in the twenty-first century. Finally, the paper observes that India's role in East Asia does not have to be fundamentally defined by or structured on the basis of the actions of a third party.